Human genome editing in clinical applications: Japanese lay and expert attitudes - Sawai, Tsutomu; Hatta, Taichi; Akatsuka, Kyoko; Fujita, Misao (Frontiers in Genetics, 2023)
Background: The world's first gene-edited babies, reported by the Chinese scientist He Jiankui, prompted an outcry of criticism and concerns worldwide over the use of genome editing for reproductive purposes. Many countries and academic associations opposed to heritable genome editing (HGE) called for public discussion involving various stakeholders. To hold a discussion of this nature and form a consensus concerning HGE, we must understand under what conditions stakeholders consider HGE acceptable and the reasons for which they deem it unacceptable.Methods: Laypeople and researchers were surveyed in May 2019. They were asked about the degree of their acceptance toward somatic genome editing (SGE) and HGE; those who answered "acceptable depending on the purpose" were queried further regarding their acceptance in the contexts of specific clinical purposes. This is a provisional file, not the final typeset article was similar to that of the lay participants, with 12.7, 9.1, 10.9, and 5.5% for physical, cognitive, health, and personality enhancement, respectively. Conclusion: In the past, debates regarding the acceptability of human genome editing in clinical applications tend to focus on HGE in many countries. Society will now need to debate the acceptability of both types of human genome editing, HGE and SGE.